Kebijakan Eksistensi Peradilan Adat di Kabupaten Fakfak - Suriadi; Kadek Wiwik Indrayanti (MLJ Merdeka Law Journal, 2026)
This research aims to examine the existence of Customary Courts in Fakfak Regency from a National Law perspective and to analyze the role of customary law institutions in resolving customary disputes following the enactment of Law Number 2 of 2021 concerning the Second Amendment to Law Number 21 of 2001 concerning Special Autonomy for Papua Province. Although Customary Courts have long existed and developed within indigenous communities, their existence has not been supported by a strong policy framework, either at the national or regional levels. The absence of a Special Regional Regulation in West Papua Province that explicitly regulates Customary Courts has resulted in weak legal certainty and the ineffectiveness of customary law policy implementation, even though customary dispute resolution practices continue to occur in Fakfak Regency. This research employs a normative juridical method with a statutory and conceptual approach, through a review of positive legal norms governing Customary Courts, specifically the Papuan Special Autonomy Law and other related regulations. The results indicate that Customary justice has been normatively recognized in the Indonesian legal system as a dispute resolution mechanism for indigenous communities. However, its status has not been firmly integrated into the state justice system and remains partial. Within the framework of Papua's Special Autonomy, the policy on the existence of customary justice reflects recognition of legal pluralism and the important role of customary law, but it still requires regulatory strengthening and institutional integration to be more effective and able to provide legal certainty.